UPAYA PENANGGULANGAN ILLEGAL LOGGING MELALUI HUKUM ADAT DITINJAU DARI PERSPEKTIF PLURALISME HUKUM - Muzakir Salat (Faculty of Law, Universitas Diponegoro, 2012)
The Illegal logging regulated in some positive rules, in the meanwhile act number 41/1995, act number 5/1985, The government regulation number 28/1985 and The Penal Regulation. In the those regulations not always can be solve the case of illegal loging. Traditional People with their custom law have a role to defand natural resource. Some example case were prove about that. They have local wisdom to defand riches that from their forefather. They realize that the forest give them a lot of contribution for their live resoluteness.The damage of forest that caused illegal logging will be suffered them. The traditional people have the custom law and sanction themselves that will be exictence by them for a long life natural resources. So, the pluralism with combination of the positive law and custom law is needed to solve the illegal logging.Key word : Illegal logging, custom law,pluralisme